2016
DOI: 10.4236/jmmce.2016.43020
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Talc Flotation for Different Industrial Applications

Abstract: Talc has found a steadily increasing number of uses such as cosmetics, steatite and cordierite ceramics, for pitch control in the paper industry and as a reinforcing filler in rubber, etc. In this research, the amenability of some Egyptian carboniferous finely disseminated talc ores to beneficiation by flotation was investigated on laboratory scale. The original talc sample is characterized by low MgO content (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
1
11
0
Order By: Relevance
“…The concentrate was characterized to monitor the extent of talc recovery and iron removal efficiencies. The mass and component recoveries of concentrate were determined (Ahmed, 2017;Boulos et al 2016). The concentrate obtained was further used for the leaching investigations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrate was characterized to monitor the extent of talc recovery and iron removal efficiencies. The mass and component recoveries of concentrate were determined (Ahmed, 2017;Boulos et al 2016). The concentrate obtained was further used for the leaching investigations.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental mass and component recovery of the concentrate after flotation is determined through the following relations (Boulos et al 2016):…”
Section: Methodsmentioning
confidence: 99%
“…The chemical analysis of samples showed that, iron oxide was the main gangue mineral in samples (the percent of Fe 2 O 3 = 4.96%). Boulos et. al.…”
Section: Petrographical and Geochemical Characterization Of Talcmentioning
confidence: 99%
“…For El-Allaqi sample, an attritioning scrubbing was executed at 60% solids, 2100 rpm motor speed and an attritioning time of 60 minutes. The product has 5% loss on ignition and about 87.5% mass recovery (Boulos et. al.…”
Section: Petrographical and Geochemical Characterization Of Talcmentioning
confidence: 99%
See 1 more Smart Citation